Subthreshold Depressive Symptoms have a Negative Impact on Cognitive Functioning in Middle-Aged and Older Males - Brevik, Erlend J.; Eikeland, Rune A.; Lundervold, Astri J. (Frontiers in Psychology, 2013)
Introduction. Cognitive aging is associated with a decline on measures of fluid intelligence (gF), whereas crystallized intelligence (gC) tends to remain stable. In the present study we asked if depressive symptoms might contribute to explain the decline on gF in a sample of healthy, middle-aged and older adults. Method. The Norwegian sample included 83 females and 42 males (M = 60, SD = 7.9 yrs). gF was calculated from factor-analysis, including tests of matrix reasoning (WASI), memory function (California Verbal Learning Test), processing speed and executive function (Cued Discrimination Task; Color-Word Interference Test). gC was derived from a Vocabulary subtest (WASI). Depressive symptoms were assessed by self-reports on Beck’s Depression Index (BDI) and ranged from 0 to 21 (M = 6, SD = 4.5). Results. Increased age was correlated with a decline on gF (r=-.436, p<.001), but not gC (r=-.103, p=ns.). The BDI score in the whole sample was correlated with gF (r=-.313, p<.001). A more detailed analysis showed that the BDI score correlated with measures of both gF and gC in males. The correlations were non-significant for females on all measures, with the exception of a measure of processing speed/executive function. A regression analysis including age and sex in the first step, showed that symptoms of depression significantly contributed to explain decline on gF, F(3,124)=16.653, p < .001, R² = .292, ∆R² = .054. Discussion. The results showed that symptoms of depression have a negative impact on cognitive functioning in males even when the symptom-level was below clinical threshold. This indicates that minimal symptoms of depression in older men are clinically relevant to address.